Yahoo Web Search

  1. Sort by

  1. The answer is d - on the LHS you have 2 hydrogen atoms but on the left there's 4.

    1 Answers · Science & Mathematics · 29/09/2018

  2. LHS = (cos 2x - cos x) / (cos x - 1) = [ 2cos^2(x) - 1 - cos(x)]/[cos(x) - 1...

    3 Answers · Science & Mathematics · 06/06/2018

  3. LHS = -(LHS) ---> LHS + (LHS) = 0 2(LHS) = 0 or LHS = 0

    5 Answers · Science & Mathematics · 02/05/2018

  4. ...equation is not an identity, if that is what you mean. Let y = π/2. LHS = csc(y) = csc(π/2) = 1 RHS = cot(y)sec(y) = cot(π/2)sec(π/2) The...

    6 Answers · Science & Mathematics · 21/04/2018

  5. ...want that 2^3 * 5 * 7* x = n² For this, all powers on the LHS bust be multiples of 2 [why?]. So you need an extra 2 to make 2^4...

    4 Answers · Science & Mathematics · 10/03/2018

  6. ... does not hold because 1 ≠ 2 ≠ 3 ≠ etc. for n >= 2. LHS = [n(n+1)/2][1/n] = (n+1)/2 RHS = [n!]^(1/n) Therefore [(n+1...

    2 Answers · Science & Mathematics · 15/02/2018

  7. ... is P(k + 1): 5^(k + 1) + 6^(k + 1) < 7^(k + 1) LHS = 5^(k + 1) + 6^(k + 1) = 5·5^k + 6·6^k = 5(5^k + 6^k) + 6^k RHS = 7...

    4 Answers · Science & Mathematics · 05/03/2018

  8. ... to ensure no root is lost. (because sinx between -1 and 1, ditto for the LHS quadratic, and after solving for x: 1.29 < x <...

    3 Answers · Science & Mathematics · 28/01/2018

  9. Your expression is an identity and not an equation LHS = (x + y)^-2 = 1/(x + y)^2 = 1/[ x(1 + y/x)]^2 = 1/x^2(1 + y/x)^2 = x^-2(1 + y/x)^-2 = RHS

    1 Answers · Science & Mathematics · 17/01/2018

  10. ...0; inequality becomes x(x + 1)² + y(y + 1)² ≥ 8xy; expand LHS: x³ + y³ + 2x² + 2y² + x + y = x³ + y³...

    2 Answers · Science & Mathematics · 17/01/2018

  1. Ad
    related to LHS
  1. Try asking your question on Yahoo Answers